Can growth stabilize debt? A fiscal theory perspective - Michaela Elfsbacka Schmöller; Nigel McClung (Bank of Finland, 2024)
This paper studies price stability and debt sustainability when the real rate exceeds trend growth (r > g) in a New Keynesian model with endogenous technology growth through R&D. Endogenous growth constitutes a self-financing mechanism for deficits which backs debt and attenuates fiscal inflation. A dynamic r - g stability criterion characterizes the set of feasible monetary-fiscal frameworks. If surpluses do not adjust to stabilize debt, the central bank must permit r - g to fall with inflation. Monetary policy which follows the Taylor principle can be consistent with a unique stable equilibrium under active fiscal policy as growth endogenously creates fiscal capacity and policy space.
urn:nbn:fi-fe202401173095
Keywords: E31; E52; E62; E24; O42; 330; Public Debt; Inflation; Monetary-Fiscal Interaction; Fiscal Theory of the Price Level; Endogenous Growth